Open innovation and its effects on economic and sustainability innovation performance - Romana Rauter; Dietfried Globocnik; Elke Perl-Vorbach; Rupert J. Baumgartner (Journal of Innovation & Knowledge (JIK), 2019)
The increasing complexity of products and services, rapidly changing market demands, or growing pressure from various societal groups are trends that require companies to enact new practices to remain competitive. The external search for information and its integration in the context of open innovation is one practice that can lead to increased success. However, the full range of potential open innovation partners has not yet been sufficiently explored, and their effects on innovation performance remain unclear. In this research, we investigated the roles different open innovation partners played in improving economic innovation performance and sustainability innovation performance. Furthermore, we asked whether striving to meet economic and sustainability innovation goals represents a conflict. Drawing on a cross-sectional sample of industrial firms and applying a benchmark approach to identify the relevant performance drivers, we found that, in addition to well-known partners such as universities and customers, increased collaboration with NGOs and intermediaries is beneficial for firms. Moreover, economic innovation performance positively correlates with sustainability innovation performance. This implies that economic and sustainability innovation goals can be reached simultaneously. Thereby, this paper contributes to the open innovation literature by revealing which collaboration partners fit best to strengthen innovation performance, and by clarifying the relationship between economic and sustainability innovation performance.
Keywords: O31; 650; Open innovation; Sustainability innovation performance; Economic innovation performance; Benchmark